Clinical biochemistry parameters in C57BL/6J mice after blood collection from the submandibular vein and retroorbital plexus - Fernandez, Itziar; Pena, Arantza; Teso, Nahia Del; Perez, Virginia; Rodriguez-Cuesta, Juan (Journal of the American Association for Laboratory Animal Science, 2010)
Collection of blood from the submandibular vein allows simple and rapid processing of many animals without anesthesia and facilitates rapid recovery with no signs of pain and discomfort in the mice. Here we compared the submandibular vein and retroorbital plexus blood collection methods, to determine the potential effect of the sampling technique on several clinical biochemistry parameters in C57BL/6J mice. We found statistically significant differences for 8 of the 9 biochemical parameters studied between the 2 blood sampling techniques. Compared with samples collected from the retroorbital plexus, blood obtained from the submadibular vein had higher levels of AST, ALT, protein, albumin, triglycerides, total cholesterol, and creatinine. Glucose values of retroorbital blood were higher than those from the submandibular vein. Urea levels were similar for both sampling techniques. Our results demonstrate that the technique used to obtain blood samples affects parameters commonly used to assess animal health. We recommend caution when comparing results of biochemical analysis of blood obtained from the submandibular vein in mice with reference values obtained by other blood sampling techniques.